2021
DOI: 10.1016/j.atmosenv.2021.118627
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the first induced COVID-19 lockdown on air quality in Israel

Abstract: The coronavirus disease 2019 (COVID-19) induced a lockdown that has resulted in a sharp reduction in air and motor traffic and industrial activities. This in turn led to a reduction in air pollution around the world. It is important to quantify the extent of that reduction in order to estimate the weight of the impact of air and motor traffic and industrial activities over the total variation of air quality. An assessment of the extent of air pollution is aimed at facilitating the crafting of policies toward t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Similar observations were reported in the conducted studies in Rio de Janeiro ( Siciliano et al, 2020 ), Hanoi ( Nguyen et al, 2022 ), Baghdad ( Hashim et al, 2021 ), Tel-Aviv ( Agami and Dayan, 2021 ), Barcelona ( Tobías et al, 2020 ), Almaty ( Kerimray et al, 2020 ), and Jiangsu ( Bhatti et al, 2021 ). When the lockdown period started, the number of emission sources, volume of road traffic, and the air pollutants (PM 2.5 and NO X ) concentrations were dropped ( Wang et al, 2021b ); dropping in NO X and VOC-limited background, resulted in higher O 3 levels ( Tobías et al, 2020 ).…”
Section: Resultssupporting
confidence: 88%
“…Similar observations were reported in the conducted studies in Rio de Janeiro ( Siciliano et al, 2020 ), Hanoi ( Nguyen et al, 2022 ), Baghdad ( Hashim et al, 2021 ), Tel-Aviv ( Agami and Dayan, 2021 ), Barcelona ( Tobías et al, 2020 ), Almaty ( Kerimray et al, 2020 ), and Jiangsu ( Bhatti et al, 2021 ). When the lockdown period started, the number of emission sources, volume of road traffic, and the air pollutants (PM 2.5 and NO X ) concentrations were dropped ( Wang et al, 2021b ); dropping in NO X and VOC-limited background, resulted in higher O 3 levels ( Tobías et al, 2020 ).…”
Section: Resultssupporting
confidence: 88%
“…Some studies in other countries and regions also reveal the important role of meteorological conditions in air quality changes. A study of Israel showed that the total percentage change of pollution emissions explained by the lockdown was up to 26%, which increased to 47% by taking meteorological conditions as a factor in addition to the lockdown effect ( Agami and Dayan, 2021 ). In India, Mandal et al (2022) noted that adverse meteorological conditions exacerbated Delhi's air pollution situation.…”
Section: Resultsmentioning
confidence: 99%
“…The cost-reduction indicates that the higher air quality has a positive association with human activity, lower traffic and the closure of factories which all causes reduce consumption of energy (Tian et al 2021 ) and provides a better air quality (Agami and Dayan 2021 ) in the different areas within the world. A comparative study on fuel consumption in Israel indicated that with extensive COVID-19 in the world, the consumption of gasoline and natural gas was reduced −22.5% and −10% respectively than the same period within 2019.…”
Section: Resultsmentioning
confidence: 99%